Building Vocabulary and Confidence in Speaking through Alphabet Box Learning in EFL Classrooms - Sonya Veningsih Cheryanti Benu; Adi B. W. Banu; Rosalina S. S. Son; Berthi O. Tunu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research focuses on improving English vocabulary and speaking confidence among students in English as a Foreign Language (EFL) classrooms through the implementation of Alphabet Box Learning. Many EFL students struggle with limited vocabulary and a lack of confidence when speaking, which hinders their communicative competence. The objective of this study was to examine the effectiveness of Alphabet Box Learning in addressing these problems by providing an engaging and student-centered learning experience. The study employed a quasi-experimental method involving 65 students of SMP Kristen 1 Soe. Data were collected through pre-tests and post-tests, classroom observations, and student questionnaires to assess improvements in vocabulary mastery and speaking confidence. The findings revealed that students who participated in Alphabet Box Learning activities showed significant gains in vocabulary acquisition and their willingness to speak in class were increased. The interactive nature of the method, which combines visual, tactile, and verbal elements, created a supportive environment that encouraged active participation and reduced speaking anxiety. In conclusion, Alphabet Box Learning is an effective instructional strategy for enhancing both vocabulary and speaking confidence among EFL learners. Its implementation provides meaningful, engaging, and low-anxiety language learning experiences, making it a valuable addition to communicative language teaching practices.